(untitled) (Central Asian Journal of Medical Sciences, 2016)
The "International Expert Consultation on Understanding and Addressing the Impact of Air Pollution on Child Health in Mongolia" was held in Ulaanbaatar, Mongolia on January 25-26, 2016. Even though conferences on environmental issues including air pollution are held in Ulaanbaatar, the air pollution situation seems to change very little. Astounding concentrations of air pollutants have become normal in the winter season of Ulaanbaatar, yet this city receives less media attention compared to Delhi, India or Beijing, China. Figure 1 shows a comparison of monthly average concentrations of one type of air pollutant, particulate matter of 2.5 micrometers or less in size (PM2.5), for November 2015 through April 2016 in the aforementioned cities. It can be seen here that PM2.5 concentrations are comparable between all three cities and even Beijing had much lower PM2.5 concentrations in January and February then the two other cities (maybe due to the Lunar New Year celebrations). Also note that these concentrations are averages from just one location in each city. Ulaanbaatar, Beijing, and Delhi have annual PM2.5 averageswell above the World Health Organization’s (WHO) guideline of 10 g/m3. This seems to suggest that air pollution is winning the battle in these cities and unfortunately many other cities in the developing world.